Pemanfaatan Instagram Bagi Pengembangan Pemasaran di Institut Banten - Mulyadi Amin; Deden Sunandar; Devi Wardiyanti (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
Not all business products are widely known by the public. One example is the Banten Institute, an business that operates in the education sector and has been operating for 14 years by utilizing Instagram social media via the @institut_banten account. This research uses a qualitative descriptive method, where the researcher attempts to describe and analyze data obtained in the field according to the focus of the problem being studied. Data and information were collected through interviews with craftsmen and account owners who were the objects of research, as well as through observations during research activities. The research results show that the use of Instagram social media has had a positive impact on the development of Banten Institute product marketing, which can be seen from the increase in the number of followers and sales. Apart from that, the ease of operation and large number of users make Instagram a practical, cheap and effective promotional medium for reaching audiences anywhere. However, this research also identified several obstacles, such as poor internet access in the account owner's location, limited expertise of the account owner in creating attractive designs, and the absence of product prices, which require consumers to communicate via the contacts provided.